HOMOSOSIALITAS DI PONDOK PESANTREN: STUDI KASUS DI PONDOK PESANTREN AS-SAKAN - Sudrajat Nur, Gian Nova; Priyatna, Aquarini; Zakaria, Mumuh Muhsin (HUMANIKA, 2016)
This paper discusses the homosexual practices among students at Pondok Pesantren As-Sakan. By using queer and homosociality theory, the paper will show that human sexuality is a very complex continuum, in which homosexual practices can be manifested in various forms. It will be shown that same-sex relationships are built on male friendship patterns among men, mentorship, entilement, competition between homosexuality and heterosexuality in intimate relationships so that there is a shift in the relationship in it. The practice of sex segregation which is part of the normative practice of the boarding school, manifested in, for example, activities, rules and sanctions, as well as facilities and infrastructure of the school, can be argued to have engendered practices that can be categorized as homosexual practices.